Signifikansi Proses Pencarian Makna terhadap Teks Agama: Menyibak Pemikiran Nasr Hamid Abu Zaid - Muzakki, Akhmad (UIN Maulana Malik Ibrahim Malang, 2006)
Basically, according to Gadamer, words belong to and are based on the reality. Human beings look for the appropriate words to express the reality. Ontologically; human beings do not create language as a means of communication and thinking, but it was created more as the representation of reality while they articulated the language. Therefore, the meaning of words exists in the thought. According to Saksitri’s theory, a word is considered as sign related to signifiant (something signifying) and signifie (something signified). Signifiant explains the form or expression, and signifie explains the thought or meaning. The relation, brtween signifiant and signifie based on the social convention is called significance or maghza according to Nasr Hamid. On the other words, significance is an effort to give meaning to sign (language). According to linguists,such as Jacques Derrida, the last signifie is not